Molecular deletion analysis in Duchenne muscular dystrophy. Issue 6 (December 1986) - Thomas, N S; Ray, P N; Worton, R G; Harper, P S
Abstract : Study of 165 unrelated patients with X linked muscular dystrophy (117 with Duchenne and 48 with Becker dystrophy) has shown nine Duchenne cases (8% of the total) where a molecular deletion was detected using probes pERT87 or XJ1.1. No cytogenetic abnormalities were detectable in this unselected series of patients and no clear clinical or other differences were found between deletion and non-deletion cases. No deletions were found in the 48 Becker patients. Analysis of the families allowed unequivocal identification carrier status in females hemizygous for the deleted allele. Since some of the deletions were detected with only one of the two probes, it is important that both pERT87 and XJ1.1 are used when studying patients for molecular deletions.